THE CONCEPT OF QUR'ANIC THINKING AND ITS IMPLICATIONS FOR THE FORMATION OF CRITICAL ATTITUDES IN DA’WAH - Ahmad Hayyan Najikh (Indonesian Journal of Islamic Communication, 2024)
In the modern era, which is full of information and diverse currents of thought, critical thinking is an essential skill for a da’i. The Qur'an, as the main source of Islamic teachings, contains many verses that encourage its followers to think critically and reflectively. This study aims to examine the concept of Qur'anic thinking and its implications for the formation of critical attitudes in da’wah. This research uses a qualitative method with a literature study approach. Data is collected from various sources, such as the Qur'an, hadith, tafsir books, and scientific works related to the topic. This study finds that the concept of Qur'anic thinking has significant implications for the formation of critical attitudes in da’wah. Concepts such as questioning assumptions, seeking evidence, being open to different perspectives, and using reason and logic become the basis for preachers to deliver effective and enlightening preaching. This study concludes that the concept of Qur'anic thinking needs to be integrated into the process of learning and training preachers. This is expected to produce competent da’i who are able to answer the challenges of the times in da’wah.